2001
DOI: 10.1161/01.res.88.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Murine Models of Familial Hypertrophic Cardiomyopathy

Abstract: Although sarcomere protein gene mutations cause familial hypertrophic cardiomyopathy (FHC), individuals bearing a mutant cardiac myosin binding protein C (MyBP-C) gene usually have a better prognosis than individuals bearing beta-cardiac myosin heavy chain (MHC) gene mutations. Heterozygous mice bearing a cardiac MHC missense mutation (alphaMHC(403/+) or a cardiac MyBP-C mutation (MyBP-C(t/+)) were constructed as murine FHC models using homologous recombination in embryonic stem cells. We have compared cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
119
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 26 publications
12
119
2
Order By: Relevance
“…This mimics the human disease very closely. Further studies in a second mouse model of HCM in which the myosin-binding protein C gene is truncated using a targeted construct with a Neo cassette, confirms the human finding that disease occurs much later in life, with the myosin-binding protein C mice showing hypertrophy in only 30% of mice at age 30 weeks (versus 100% with hypertrophy in Arg403Gln myosin mice at the same age) but all mice developing disease by age 2 years [60]. Such comparison between models will be invaluable in addressing the issues of disease heterogeneity and penetrance, as well as the effects of aging in the progression of cardiomyopathy.…”
Section: Animal Modelssupporting
confidence: 55%
See 2 more Smart Citations
“…This mimics the human disease very closely. Further studies in a second mouse model of HCM in which the myosin-binding protein C gene is truncated using a targeted construct with a Neo cassette, confirms the human finding that disease occurs much later in life, with the myosin-binding protein C mice showing hypertrophy in only 30% of mice at age 30 weeks (versus 100% with hypertrophy in Arg403Gln myosin mice at the same age) but all mice developing disease by age 2 years [60]. Such comparison between models will be invaluable in addressing the issues of disease heterogeneity and penetrance, as well as the effects of aging in the progression of cardiomyopathy.…”
Section: Animal Modelssupporting
confidence: 55%
“…Analysis of the phenotype in these heterozygous Arg403Gln mice has revealed features which parallel the human disease (summarised in Tab 2). In brief, Arg403Gln mice develop classical histopathological changes of HCM (myocyte hypertrophy, disarray and fibrosis) by age 15 weeks, and echocardiographically detectable left ventricular hypertrophy by 30 weeks [60]. This mimics the human disease very closely.…”
Section: Animal Modelsmentioning
confidence: 88%
See 1 more Smart Citation
“…The increase in HW/ BW ratio in post-MI rats was consistent with the presence of enlarged cardiomyocytes (cross-sectional width 32.1±0.8µm to compare with sham: 23.5 ± 0.6 µm; P<0.05, Fig.3b), next to interstitial collagen deposits in the noninfarcted LV. Fibrosis (Fig.3c) and re-expression of fetal atrial natriuretic peptide (ANP) and myosin heavy chain (MHC)-ß isoform genes (Fig.3d) attested to pathological hypertrophy [36][37][38][39]. One-month NAC treatment did not lessen hypertrophy (Fig.3a).…”
Section: In Post-mi Rats 1-month Nac Treatment Replenished LV Glutatmentioning
confidence: 97%
“…Initial studies of genetically outbred MHC 403/ϩ mice demonstrated variable degrees of hypertrophy and histopathology (19)(20)(21)(22). To control for the influence of background genotype on disease expression, we bred the MHC 403/ϩ allele into the inbred 129SvEv genetic background and investigated the relationship between histopathology and arrhythmia vulnerability in hypertrophic mice using in vivo and ex vivo electrophysiological studies (23,24).…”
mentioning
confidence: 99%